Jeszcze raz o Kolumbach rosyjskiej prowincji (Podróż wokół Moskwy Nikołaja Karamzina, Podróż do Kronsztadu Piotra Szalikowa i Podróż do południowej Rosji Władimira Izmajłowa) - Dąbrowska, Magdalena (Przegląd Rusycystyczny, 2009)
ЕЩЕ РАЗ О КОЛУМБАХ РУССКОЙ ПРОВИНЦИИ (ПУТЕШЕСТВИЕ ВОКРУГ МОСКВЫ Н. КАРАМЗИНА, ПУТЕШЕСТВИЕ В КРОНШТАДТ П. ШАЛИКОВА И ПУТЕШЕСТВИЕ В ПОЛУДЕННУЮ РОССИЮ В. ИЗМАЙЛОВА) Резюме Провинциальная Россия — окрестности Москвы и Петербурга, а также „полуден-ная Россия” — крупное литературно-географическое открытые XVIII века. Об этом свидетельствуют Путешествие вокруг Москвы (1803) Н.М. Карамзина, Путешес-твие в Кpонштадт... (1806) П.И. Шаликова и Путешествие в полуденную Россию (1800–1802, 1805) В.В. Измайлова. Сентименталисты приводят в них исторические (деятельность Петра I и Екатерины II), а также географические, культурно-социоло-гические и этнографические сведения. A FEW MORE WORDS ON RUSSIAN PROVINCE COLUMBUSES (JOURNEY AROUND MOSCOW BY N. KARAMZIN, JOURNEY TO KRONSTADT BY P. SHALIKHOV AND JOURNEY TO THE SOUTHERN RUSSIA BY V. IZMAJLOV) Summary The provincial Russia — both the surroundings of the capitals (Moscow and Petersburg) and the distant guberniyas (including the Southern territories) — was a big 18th century literary and geographical discovery, as evidenced by the Journey around Moscow (1803) by N.M. Karamzin, Journey to Kronstadt... (1806) by P.I. Shalikhov and Journey to the Southern Russia (1800–1802, 1805) by V.V. Izmajlov. Those writers remind there of the historic events (including the reins of Peter I and Catherine II) and provide information on geography, cul-ture, ethnography and sociology.